APPLICATION SYSTEM SALES TOOLS IN STORES BATIK HDM USING MICROSOFT VISUAL BASIC 6.0 - Dewi Maryana (Jurnal Sistem Informasi, 2010)
Scientific writing contains a simple program on computerization sales batik,using input goods through the production and sales process, which will thenautomatically stored in a database and display the output results will come outthat will be received by the customer or purchaser as the invoice or receipt andview reports required by the batik businessman . The process of inputting andsales of computerized this makes data processing more efficient and accurateand can provide information on existing inventory.